Discovery of potent and selective activity-based probes (ABPs) for the deubiquitinating enzyme USP30 - Mondal,M; Cao,F; Conole,D; Auner,H; Tate,E (RSC Chemical Biology, 2024)
Ubiquitin-specific protease 30 (USP30) is a deubiquitinating enzyme (DUB) localized at the mitochondrial outer membrane and involved in PINK1/Parkin-mediated mitophagy, pexophagy, BAX/BAK-dependent apoptosis, and IKKβ-USP30-ACLY-regulated lipogenesis/tumorigenesis. A USP30 inhibitor, MTX652, has recently entered clinical trials as a potential treatment for mitochondrial dysfunction. Small molecule activity-based probes (ABPs) for DUBs have recently emerged as powerful tools for in-cell inhibitor screening and DUB activity analysis, and here, we report the first small molecule ABPs (IMP-2587 and IMP-2586) which can profile USP30 activity in cells. Target engagement studies demonstrate that IMP-2587 and IMP-2586 engage active USP30 at nanomolar concentration after only 10 min incubation time in intact cells, dependent on the presence of the USP30 catalytic cysteine. Interestingly, proteomics analyses revealed that DESI1 and DESI2, small ubiquitin-related modifier (SUMO) proteases, can also be engaged by these probes, further suggesting a novel approach to develop DESI ABPs.